A core-shell graded nanoarray coating membrane and preparation method thereof
By using core-shell graded nanoarray coating on the lithium-ion battery separator, combining inorganic ceramic particles and boehmite nanoarrays and high porosity binder, the safety performance and porosity problems of lithium-ion battery separator at high temperatures are solved. , improves the safety and stability of the battery and the penetration capacity of the electrolyte.
Patent Information
- Application Number
- CN202411220867.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-02
AI Technical Summary
At this stage, the safety performance of lithium-ion battery separators at high temperatures is poor, and the coating modification of inorganic material dispersed slurry has mechanical wear and electrolyte penetration problems, making it difficult to have high heat resistance and high porosity performance.
Core-shell graded nanoarray coating membrane is used to construct boehmite nanoarrays on the surface of inorganic ceramic particles and combine with high porosity non-agglomerate adhesives to form core-shell graded nanoarray morphology, reducing the weight and resistance of the membrane. Improve electrolyte penetration and lithium ion penetration capabilities.
It extends the service life of the coating machine, improves the wettability and porosity of the separator, improves the safety and stability of the lithium battery and the penetration capacity of the electrolyte, and enhances the lithium ion transmission efficiency.
Smart Images

Figure CN118763355B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery separators, and in particular to a core-shell graded nanoarray coating separator and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are hailed as one of the most reliable technologies to solve the energy crisis and alleviate environmental pressure. However, with the expansion of lithium-ion battery applications, the defects of lithium-ion battery technology at this stage have gradually emerged. Many researchers have begun to start from the battery structure and gradually optimize lithium-ion batteries. Lithium-ion battery separators are a very important part of the battery structure, mainly providing "isolation" and "transmission" functions. The separator plays a vital role in ensuring battery safety. At present, polyolefin separators such as polyethylene (PE), polypropylene (PP) and PP / PE / PP three-layer separators have been widely used in commercial lithium batteries due to their excellent mechanical properties, excellent electrochemical stability and suitable shutdown temperature. However, the poor wettability of polyolefin separators to polar liquid electrolytes and poor thermal dimensional stability seriously affect the safety performance of lithium batteries at high temperatures.
[0003] At present, due to the thermal stability, chemical stability and wettability of inorganic materials, and the mature preparation process of their dispersed slurry, the use of inorganic dispersed slurry for membrane coating modification is a hot topic in the research of membrane modification. Among them, inorganic ceramics such as Al2O3, ZrO2, and SiO2 have attracted widespread attention due to their advantages such as low price and high wettability, and are ideal membrane modification materials. Usually, polymers such as polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN) and polymethyl methacrylate (PMMA) are used as binders for inorganic ceramic materials to coat the membrane. However, the coating modification method has certain challenges: first, the commonly used inorganic particles such as Al2O3 are easy to increase the weight of the membrane due to their own properties, and the high hardness is easy to cause wear of mechanical equipment such as coating machines. The stacking of relatively regular inorganic particles is easy to cause the weight of the membrane to increase further and hinder the insertion and removal of lithium ions; in addition, the accumulation of various adhesives is often ignored, which hinders the penetration of the electrolyte. Therefore, designing and developing a diaphragm coating with both high heat resistance and high porosity performance is an urgent problem to be solved in lithium battery coated diaphragms.
[0004] Therefore, the inventors provide a core-shell hierarchical nanoarray coating membrane and a preparation method thereof. Summary of the invention
[0005] (1) Technical issues to be resolved
[0006] The embodiment of the present invention provides a core-shell graded nanoarray coating diaphragm and a preparation method thereof, which solves the technical problem of low heat resistance and porosity performance of lithium battery coating diaphragm.
[0007] (2) Technical solution
[0008] The first aspect of the present invention provides a core-shell graded nanoarray coating diaphragm, comprising a base film, a core-shell graded nanoarray layer and a binder, wherein the core-shell graded nanoarray layer is fixed to the upper end surface of the base film by the binder, and the core-shell graded nanoarray layer is a core-shell graded nanoarray morphology composed of inorganic ceramic particles as the core and boehmite nanoarray as the shell.
[0009] Furthermore, the binder is in a non-agglomerated state with high porosity.
[0010] Furthermore, the inorganic ceramic particles are any one of Al2O3, ZrO2, SiO2, TiO2 and ZnO2.
[0011] Furthermore, the particle size of the inorganic ceramic particles is 100-150 nm.
[0012] Furthermore, the binder is at least one of polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyperfluoropropylene and polychlorotrifluoroethylene.
[0013] The second aspect of the present invention provides a method for preparing a core-shell hierarchical nanoarray coating membrane, comprising the following steps:
[0014] The inorganic ceramic particles are ground into balls using a ball mill;
[0015] Surface modification of spherical inorganic ceramic particles;
[0016] Using the surface-modified inorganic ceramic particles as cores, constructing boehmite nanoarrays on their surfaces, and obtaining inorganic ceramic materials in the form of core-shell hierarchical nanoarrays;
[0017] Weigh the core-shell hierarchical nanoarray inorganic ceramic material, binder, salt, deionized water and solvent in proportion, mix and disperse them uniformly to obtain a coating liquid;
[0018] The coating liquid is applied on a base film, and is sequentially subjected to freezing, freeze drying, deionized water soaking and room temperature drying to obtain a coating membrane.
[0019] Furthermore, the surface modification of the spherical inorganic ceramic particles is specifically performed as follows:
[0020] The polished inorganic ceramic particles were continuously stirred in an acetone solution, and were repeatedly washed with deionized water and dried.
[0021] Furthermore, the surface-modified inorganic ceramic particles are used as cores, and boehmite nanoarrays are constructed on the surface to obtain a core-shell hierarchical nanoarray inorganic ceramic material, which specifically includes the following steps:
[0022] Ultrasonic dissolution was performed according to the mass ratio of inorganic ceramic particles: DL-aspartic acid: water of 1.5:1:1 to obtain emulsion A;
[0023] Solution B was prepared according to the molar ratio of PEG4000: aluminum nitrate of 5:1;
[0024] Solution C was prepared according to the molar ratio of urea to aluminum nitrate of 50:1;
[0025] Adding the solution B to the emulsion A and continuously stirring, and then continuously adding the solution C and stirring to obtain a mixed solution;
[0026] The mixed solution is transferred to a reflux device, and heated at a set heating rate from room temperature until boiling under stirring conditions, and the heating is stopped after the system is kept boiling for a preset time;
[0027] After cooling naturally to room temperature, the precipitate is separated by heating, and the precipitate is collected by centrifugation with deionized water and ethanol in turn and washed repeatedly, and finally vacuum dried to obtain the core-shell hierarchical nano-array inorganic ceramic material.
[0028] Furthermore, the volume ratio of the emulsion A: the solution B: the solution C is 9:10:1.
[0029] Furthermore, the core-shell hierarchical nanoarray inorganic ceramic material, binder, salt, deionized water and solvent are weighed in proportion, mixed and dispersed evenly to obtain a coating liquid, which specifically includes the following steps:
[0030] Weigh inorganic ceramic material: binder: salt: deionized water in a weight ratio of 8:1:1:1 for use;
[0031] Dissolving the binder in N,N-dimethylformamide, and sequentially stirring at high speed and continuously ultrasonicating to form a clear solution;
[0032] The inorganic ceramic material, the salt and the deionized water are continuously ground, and then the clarified solution is added and continuously stirred to form the coating solution.
[0033] (3) Beneficial effects
[0034] In summary, the present invention arranges an array-distributed nano-boehmite on the outer surface of the inorganic ceramic particle material. The shell-like boehmite with surface hardness will not easily cause wear of the coating machinery, which can extend the service life of the mechanical equipment. The core-shell nano-array inorganic ceramic material is not easy to stack and agglomerate, which reduces the weight of the diaphragm in disguise, helps to accelerate the penetration of electrolyte and lithium ion transmission, improves the wettability, porosity and lithium ion penetration ability of the coating diaphragm, and further improves the safety and stability of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments of the present invention are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 It is a schematic flow chart of a method for preparing a core-shell hierarchical nanoarray coating membrane provided by an embodiment of the present invention;
[0037] Figure 2 It is a schematic structural diagram of a high heat-resistant, high-porosity coating diaphragm provided in an embodiment of the present invention;
[0038] Figure 3 This is a micron-scale SEM image of a core-shell nanoarray Al2O3@AlOOH inorganic ceramic material provided in Example 1 of the present invention;
[0039] Figure 4 This is a nanoscale SEM image of a core-shell nanoarray Al2O3@AlOOH inorganic ceramic material provided in Example 1 of the present invention.
[0040] In the figure:
[0041] 1-base film; 2-core-shell hierarchical nanoarray layer; 3-binder. DETAILED DESCRIPTION
[0042] The following detailed description of the embodiments of the present invention is provided in conjunction with the accompanying drawings and examples. The following detailed description of the embodiments and the accompanying drawings are used to illustrate the principles of the present invention, but cannot be used to limit the scope of the present invention, that is, the present invention is not limited to the described embodiments.
[0043] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0044] Figure 1 is a schematic diagram of the structure of a core-shell hierarchical nanoarray coating membrane provided by an embodiment of the present invention, such as Figure 1 As shown, the diaphragm may include a base film 1, a core-shell graded nanoarray layer 2 and a binder 3. The core-shell graded nanoarray layer 2 is fixed to the upper end surface of the base film 1 by the binder 3. The core-shell graded nanoarray layer 2 is in the form of a core-shell graded nanoarray composed of inorganic ceramic particles as the core and boehmite nanoarray as the shell.
[0045] In the above-mentioned embodiment, by arranging an array-distributed nano-scale boehmite on the outer surface of the inorganic ceramic particle material, the shell-like boehmite with surface hardness will not easily cause wear of the coating machinery, which can extend the service life of the mechanical equipment. The core-shell nano-array inorganic ceramic material is not easy to stack and agglomerate, which reduces the weight of the diaphragm in disguise, helps to accelerate the penetration of the electrolyte and the transmission of lithium ions, improves the wettability, porosity and lithium ion penetration ability of the coating diaphragm, and further improves the safety and stability of the lithium battery.
[0046] Among them, the base film 1 is a base film such as polyethylene (PE), polypropylene (PP) or PP / PE / PP three-layer diaphragm. The specific structure of the core-shell graded nanoarray layer 2 is similar to that of sea urchin, the inorganic ceramic particles are spherical, and the nano-scale boehmite array is distributed on the surface of the sphere. The binder 3 is a high-porosity non-agglomerated form (that is, a porous binder), thereby increasing the high porosity of the binder 3 to accelerate the penetration of the electrolyte. The binder 3 can specifically be at least one of polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyperfluoropropylene and polychlorotrifluoroethylene.
[0047] As an optional embodiment, the inorganic ceramic particles are any one of Al2O3, ZrO2, SiO2, TiO2 and ZnO2, and the particle size of the inorganic ceramic particles is 100-150nm. The inorganic ceramic particles can be any one of the inorganic nanoparticles as long as they meet the requirements.
[0048] Figure 2 is a schematic diagram of a process for preparing a core-shell hierarchical nanoarray coating membrane provided by an embodiment of the present invention, such as Figure 2 As shown, the method may include the following steps:
[0049] S100, grinding the inorganic ceramic particles into a spherical shape using a ball mill;
[0050] S200, surface modification of spherical inorganic ceramic particles;
[0051] S300, using the surface-modified inorganic ceramic particles as cores, constructing boehmite nanoarrays on their surfaces to obtain core-shell graded nanoarray inorganic ceramic materials;
[0052] S400, weighing the core-shell graded nano-array inorganic ceramic material, the binder, salt, deionized water and the solvent in proportion, mixing them, and dispersing them evenly to obtain a coating liquid;
[0053] S500, coating the coating liquid on the base film, and sequentially subjecting the base film to freezing, freeze drying, deionized water soaking and room temperature drying to obtain a coating membrane.
[0054] In the above embodiment, in step S200, the surface of the spherical inorganic ceramic particles is modified, specifically, the polished inorganic ceramic particles are continuously stirred in an acetone solution, and are repeatedly washed with deionized water and dried.
[0055] In step S300, the surface-modified inorganic ceramic particles are used as cores, and boehmite (AlOOH) nanoarrays are constructed on their surfaces to obtain a core-shell graded nanoarray inorganic ceramic material, which specifically includes the following steps:
[0056] S301, performing ultrasonic dissolution according to a mass ratio of inorganic ceramic particles: DL-aspartic acid: water of 1.5:1:1 to obtain emulsion A;
[0057] S302, preparing solution B according to the molar ratio of PEG4000:aluminum nitrate of 5:1;
[0058] S303, preparing solution C according to the molar ratio of urea to aluminum nitrate of 50:1;
[0059] S304, adding solution B to emulsion A and continuing to stir, and then continuing to add solution C and stirring to obtain a mixed solution;
[0060] S305, transferring the mixed solution to a reflux device, heating it from room temperature at a set heating rate under stirring until boiling, and stopping heating after the system is kept boiling for a preset time;
[0061] S306, after cooling naturally to room temperature, heat and separate the precipitate, collect the precipitate by centrifugation with deionized water and ethanol in turn, wash repeatedly, and finally vacuum dry to obtain a core-shell hierarchical nano-array inorganic ceramic material.
[0062] As an optional embodiment, the volume ratio of emulsion A: solution B: solution C is 9:10:1. The setting of the volume ratio can satisfy the requirement that the prepared mixed solution can obtain the corresponding core-shell hierarchical nanoarray inorganic ceramic material in the subsequent heating, cooling, separation, washing and drying treatments.
[0063] In step S400, the core-shell graded nanoarray inorganic ceramic material, binder, salt, deionized water and solvent are weighed in proportion and mixed, and dispersed evenly to obtain a coating liquid, which specifically includes the following steps:
[0064] S401, weighing inorganic ceramic material: binder: salt: deionized water in a weight ratio of 8:1:1:1 for use;
[0065] S402, dissolving the binder in N,N-dimethylformamide, and sequentially stirring at high speed and continuously ultrasonicating to form a clear solution;
[0066] S403, continuously grinding the inorganic ceramic material, salt and deionized water, then adding the clarified solution, and continuously stirring to form a coating solution.
[0067] Specifically, salt water is introduced into the coating membrane as a porogen of the binder and a separation factor between inorganic ceramic materials, and salt molecules and water ice crystals are used as sacrificial templates to prepare a membrane coating with high heat resistance and high porosity.
[0068] Example 1
[0069] Preparation of Al2O3@AlOOH inorganic ceramic materials:
[0070] (1) Preparation: Using a ball mill to grind Al2O3 inorganic ceramic particles into spherical shapes, the diameter of the particles after grinding is about 100-150 nm;
[0071] (2) surface modification of the obtained inorganic ceramic particles, firstly, continuously stirring the polished Al2O3 inorganic ceramic particles in an acetone solution, and repeatedly washing with deionized water and drying;
[0072] (3) preparing emulsion A by ultrasonic dissolution of pretreated Al2O3 particles: DL-aspartic acid: water at a mass ratio of 1.5:1:1; preparing PEG4000 aqueous solution B at a molar ratio of PEG4000: aluminum nitrate of 5:1; preparing aqueous solution C at a molar ratio of urea: aluminum nitrate of 50:1; wherein the volume ratio of deionized water to emulsion A: solution B: solution C is 9:10:1;
[0073] (4) Slowly adding solution B to the obtained emulsion A and stirring for 1 hour, then slowly adding solution C and stirring to obtain a mixed solution;
[0074] (5) The obtained mixed solution is transferred to a reflux device, and slowly heated from room temperature at a heating rate of 5°C per minute until boiling under slow stirring. The system is kept boiling for a period of time and then the heating is stopped. After naturally cooling to room temperature, the precipitate is separated by heating. The precipitate is collected by centrifugation with deionized water and ethanol in turn and washed three times repeatedly. Finally, it is vacuum dried at 60°C to obtain Figure 3-4 The Al2O3@AlOOH inorganic ceramic material with a core-shell hierarchical nanoarray structure is shown;
[0075] Preparation of high heat-resistant and high porosity coating membrane:
[0076] (6) Weigh and set aside Al2O3@AlOOH inorganic ceramic material: PVDF / PAN / PMMA / PFA / FEP: salt: deionized water in a weight ratio of 8:1:1:1;
[0077] (7) Dissolve PVDF / PAN / PMMA / PFA / FEP in appropriate DMF, and sequentially stir at high speed and continuously sonicate to form a clear solution;
[0078] (8) Grinding the Al2O3@AlOOH inorganic ceramic material, salt and deionized water for 1 h, then slowly adding the clarified solution and continuously stirring to form a relatively uniform film-forming emulsion, which is then degassed and set aside;
[0079] (9) applying the emulsion on one or both sides of a base film, freezing it immediately, and then freeze-drying it, wherein the base film used is PE, PP, or PP / PE / PP;
[0080] (10) The freeze-dried coated membrane is immersed in deionized water for several hours, and this process is repeated three times to remove the precipitated salt crystals, and then dried to obtain a high heat-resistant and high porosity coated membrane finished product 1.
[0081] Example 2
[0082] Preparation of Al2O3@AlOOH inorganic ceramic materials:
[0083] The specific process is consistent with the ratio and preparation process of the Al2O3@AlOOH inorganic ceramic material in Example 1;
[0084] Preparation of high heat-resistant and high porosity coating membrane:
[0085] (1) Weigh and set aside Al2O3@AlOOH inorganic ceramic material: PAN: salt: deionized water in a weight ratio of 7:2:1:1;
[0086] (2) Dissolve PAN in an appropriate amount of DMF and sequentially stir at high speed and continue to sonicate to form a clear solution;
[0087] (3) Add Al2O3@AlOOH inorganic ceramic material, salt and deionized water into the clarified solution and continue stirring to form a film-forming emulsion with relatively uniform composition, which is then degassed and set aside for later use;
[0088] (4) applying the emulsion on one or both sides of a base film, freezing it immediately, and then freeze-drying it, wherein the base film used is PE, PP, or PP / PE / PP;
[0089] (5) The freeze-dried coated membrane was immersed in deionized water for several hours, and the process was repeated three times to remove the precipitated salt crystals, and then dried to obtain the finished product 2 of the high heat-resistant and high porosity coated membrane embodiment.
[0090] Example 3
[0091] Preparation of Al2O3@AlOOH inorganic ceramic materials:
[0092] The specific process is consistent with the ratio and preparation process of the Al2O3@AlOOH inorganic ceramic material in Example 1;
[0093] Preparation of high heat-resistant and high porosity coating membrane:
[0094] (1) Weigh and set aside Al2O3@AlOOH inorganic ceramic material: PVDF: PFA: FEP: salt: deionized water in a weight ratio of 7:1.5:1:1:1:1;
[0095] (2) Dissolve PVDF, PFA and FEP in appropriate DMF and sequentially stir at high speed and continuously sonicate to form a clear solution;
[0096] (3) Add Al2O3@AlOOH inorganic ceramic material, salt and deionized water into the clarified solution and continue stirring to form a film-forming emulsion with relatively uniform composition, which is then degassed and set aside for later use;
[0097] (4) applying the emulsion on one or both sides of a base film, freezing it immediately, and then freeze-drying it, wherein the base film used is PE, PP, or PP / PE / PP;
[0098] (5) The freeze-dried coated membrane was immersed in deionized water for several hours, and this process was repeated three times to remove the precipitated salt crystals, and then dried to obtain the finished product 3 of the high heat-resistant and high porosity coated membrane embodiment.
[0099] Example 4
[0100] Preparation of ZrO2@AlOOH inorganic ceramic materials:
[0101] (1) Preparation: Using a ball mill, ZrO2 inorganic ceramic particles are ground into spheres, and the diameter of the particles after grinding is about 100 to 150 nm;
[0102] (2) surface modification of the obtained inorganic ceramic particles, firstly, continuously stirring the polished ZrO2 inorganic ceramic particles in an acetone solution, and repeatedly washing with deionized water and drying;
[0103] (3) Pre-treated ZrO2 particles: DL-aspartic acid: water were ultrasonically dissolved in a mass ratio of 1.5:1:1 to obtain emulsion A; PEG4000 aqueous solution B was prepared in a molar ratio of PEG4000: aluminum nitrate of 5:1; aqueous solution C was prepared in a molar ratio of urea: aluminum nitrate of 50:1; wherein the volume ratio of deionized water to emulsion A: solution B: solution C was 9:10:1;
[0104] (4) Slowly adding solution B to the obtained emulsion A and stirring for 1 hour, then slowly adding solution C and stirring to obtain a mixed solution;
[0105] (5) The obtained mixed solution is transferred to a reflux device, and is slowly heated from room temperature at a heating rate of 5°C per minute until boiling under slow stirring conditions, and the system is kept boiling for a period of time before the heating is stopped; after naturally cooling to room temperature, the precipitate is separated by heating, and the precipitate is collected by centrifugation with deionized water and ethanol in turn and repeatedly washed three times, and finally vacuum dried at 60°C to obtain a ZrO2@AlOOH inorganic ceramic material with a core-shell hierarchical nanoarray structure;
[0106] Preparation of high heat-resistant and high porosity coating membrane:
[0107] (6) Weigh and set aside ZrO2@AlOOH inorganic ceramic material: PVDF / PAN / PMMA / PFA / FEP: salt: deionized water in a weight ratio of 8:1:1:1;
[0108] (7) Dissolve PVDF / PAN / PMMA / PFA / FEP in appropriate DMF, and sequentially stir at high speed and continuously sonicate to form a clear solution;
[0109] (8) Grinding the ZrO2@AlOOH inorganic ceramic material, salt and deionized water for 1 h, then slowly adding the clarified solution and continuously stirring to form a relatively uniform film-forming emulsion, which is then degassed and set aside;
[0110] (9) applying the emulsion on one or both sides of a base film, freezing it immediately, and then freeze-drying it, wherein the base film used is PE, PP, or PP / PE / PP;
[0111] (10) The freeze-dried coated membrane is immersed in deionized water for several hours, and this process is repeated three times to remove the precipitated salt crystals, and then dried to obtain the finished product 4 of the high heat-resistant and high porosity coated membrane embodiment.
[0112] Example 5
[0113] The core particles in Example 1 are replaced with SiO2 particles, and the remaining steps are the same to obtain a high heat-resistant, high-porosity coating diaphragm Example finished product 5.
[0114] Example 6
[0115] The core particles in Example 1 are replaced with TiO2 particles, and the remaining steps are the same to obtain the finished product 6 of the high heat-resistant and high porosity coating diaphragm example.
[0116] Example 7
[0117] The core particles in Example 7 are replaced with ZnO2 particles, and the remaining steps are the same to obtain the high heat-resistant and high porosity coating membrane Example finished product 7.
[0118] Example 8
[0119] (1) Al2O3@AlOOH: ZrO2@AlOOH: PVDF / PAN / PMMA / PFA / FEP: salt: deionized water are weighed and set aside in a weight ratio of 4:4:1:1:1, wherein Al2O3@AlOOH and ZrO2@AlOOH are respectively the Al2O3@AlOOH inorganic ceramic material in Example 1 and the ZrO2@AlOOH inorganic ceramic material in Example 2;
[0120] (2) Dissolve PVDF in appropriate DMF and sequentially stir at high speed and continuously sonicate to form a clear solution;
[0121] (3) Grinding the inorganic ceramic material, salt and deionized water for 1 hour, then slowly adding the clarified solution (2) and continuously stirring to form a film-forming emulsion with relatively uniform composition, which is then degassed and set aside for later use;
[0122] (4) Apply the emulsion on one or both sides of the base film, freeze it immediately, and then freeze-dry it. The base film used is PE, PP or PP / PE / PP;
[0123] (5) The freeze-dried coated membrane is immersed in deionized water for several hours, and this process is repeated three times to remove the precipitated salt crystals, and then dried to obtain a high heat-resistant and high porosity coated membrane finished product 8.
[0124] Example 9
[0125] Preparation of AlOOH inorganic ceramic materials:
[0126] (1) Degrease a high-purity 0.2 mm thick aluminum foil (30 mm × 20 mm) in acetone for 15 min, then rinse with distilled water, immerse the aluminum foil in 1 mol / L NaOH solution for 20 min to eliminate the oxide layer, and wash it four times with distilled water;
[0127] (2) In a typical hydrothermal process, 20 g of urea and 0.4 g of NaOH were dissolved in 100 mL of distilled water to obtain a transparent solution, and 60 mL of the solution was transferred to a Teflon-lined stainless steel autoclave (100 mL capacity), and the cleaned aluminum foil was immersed in the solution. The autoclave was sealed and maintained at 180 °C for 24 hours, and then naturally cooled to room temperature. The product was centrifuged and washed three times with distilled water. The prepared sample was dried in air at 80 °C for 6 hours to obtain the preparation of AlOOH inorganic ceramic material;
[0128] Preparation of high heat-resistant and high porosity coating membrane:
[0129] Replace the Al2O3@AlOOH inorganic ceramic particles in the "Preparation of high heat-resistant and high porosity coating membrane" in Example 1 with AlOOH inorganic ceramic material and follow the same remaining steps to obtain a high heat-resistant and high porosity coating membrane Example finished product 9.
[0130] Comparative Example 1
[0131] (1) Al2O3 (Al2O3 is a commercial ceramic particle with an average size of about 0.3 μm) and PVDF are weighed and set aside in a weight ratio of 8:1. PVDF is then dissolved in an appropriate amount of DMF, and then stirred at high speed and continuously ultrasonicated to form a clear solution. Subsequently, Al2O3 is continuously ground for 1 hour, and then the clear solution is slowly added and continuously stirred to form a film-forming emulsion with relatively uniform composition, which is then degassed and set aside.
[0132] (2) The emulsion is coated on one or both sides of a base film, and immediately frozen and then freeze-dried. The base film used is a PE, PP or PP / PE / PP base film. Subsequently, the cold-dried coated membrane is immersed in deionized water for several hours, and the process is repeated three times. The finished product 1 of the comparative example is dried to obtain the finished product 1.
[0133] Comparative Example 2
[0134] The Al2O3 in comparative example 1 was replaced by ZrO2, and the remaining materials and steps were the same to obtain comparative example finished product 2.
[0135] Comparative Example 3
[0136] The Al2O3 in comparative example 1 was replaced by SiO2, and the remaining materials and steps were the same to obtain comparative example finished product 3.
[0137] Comparative Example 4
[0138] The Al2O3 in comparative example 1 was replaced by TiO2, and the remaining materials and steps were the same to obtain comparative example finished product 4.
[0139] Product performance testing
[0140] The physical and chemical properties of the high heat-resistant, high-porosity coating membranes prepared in Examples 1-9 and Comparative Examples 1-5 were measured:
[0141] (1) Porosity is measured by mercury intrusion porosimeter, and the test standard is GB / T21650.2-2008;
[0142] (2) Air permeability test: Cut the prepared diaphragm into 3 cm*3 cm square pieces, put them into the test port of the Gurley tester, and measure the air permeability time, which is expressed as the Gurley value;
[0143] (3) Thermal shrinkage test: After drying the coated diaphragm, cut out a film sample of a certain size, measure its longitudinal length (MD1), put it in a precision oven and bake it at 120°C for 2 hours, take out the diaphragm sample, cool it to room temperature, measure its longitudinal length (MD2) again, and calculate the thermal shrinkage δ = (MD1-MD2) / MD1×100%;
[0144] (4) The tensile strength of the diaphragm is tested using standard GB / T1040.3-2006;
[0145] (5) The thickness of the lithium battery separator is tested according to the national standard GB / T6672-2001;
[0146] (6) The water contact angle is tested according to the national standard GB∕T 30693-2014.
[0147] The test results of the physical and chemical properties of the high heat-resistant and high-porosity coating membranes prepared in Examples 1-9 and Comparative Examples 1-5 are shown in Table 1 below:
[0148] Table 1
[0149]
[0150] It can be seen from the data in the above table that the porosity, heat resistance, tensile strength and other physical and chemical performance indicators of the core-shell hierarchical nanoarray diaphragm coating prepared by the present invention are more excellent.
[0151] It should be clear that the various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. The present invention is not limited to the specific steps and structures described above and shown in the figures. In addition, for the sake of brevity, a detailed description of known methods and technologies is omitted here.
[0152] The above are only embodiments of the present application and are not limited to the present application. For those skilled in the art, the present application may have various changes and variations without departing from the scope of the present invention. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for preparing a core-shell hierarchical nanoarray coating membrane, characterized in that: The method comprises the following steps: The inorganic ceramic particles are ground into balls using a ball mill; Surface modification of spherical inorganic ceramic particles; Using the surface-modified inorganic ceramic particles as cores, constructing boehmite nanoarrays on their surfaces, and obtaining inorganic ceramic materials in the form of core-shell hierarchical nanoarrays; Weigh the core-shell hierarchical nanoarray inorganic ceramic material, binder, salt, deionized water and solvent in proportion, mix them, and evenly disperse them to obtain a coating liquid; The coating liquid is applied on the base film, and the base film is subjected to freezing, freeze drying, deionized water soaking and room temperature drying in sequence to obtain a coating membrane; The method uses the surface-modified inorganic ceramic particles as cores, constructs boehmite nanoarrays on the surface thereof, and obtains a core-shell graded nanoarray inorganic ceramic material, which specifically includes the following steps: Ultrasonic dissolution was performed according to the mass ratio of inorganic ceramic particles: DL-aspartic acid: water of 1.5:1:1 to obtain emulsion A; Solution B was prepared according to the molar ratio of PEG4000: aluminum nitrate of 5:1; Solution C was prepared according to the molar ratio of urea to aluminum nitrate of 50:1; Adding the solution B to the emulsion A and continuously stirring, and then continuously adding the solution C and stirring to obtain a mixed solution; The mixed solution is transferred to a reflux device, and heated at a set heating rate from room temperature until boiling under stirring conditions, and the heating is stopped after the system is kept boiling for a preset time; After naturally cooling to room temperature, the precipitate is separated by heating, and the precipitate is collected by centrifugation with deionized water and ethanol in turn and repeatedly washed, and finally vacuum dried to obtain the core-shell hierarchical nano-array inorganic ceramic material.
2. The method for preparing the core-shell hierarchical nanoarray coating membrane according to claim 1, characterized in that: The surface modification of the spherical inorganic ceramic particles is specifically as follows: The polished inorganic ceramic particles were continuously stirred in an acetone solution, and were repeatedly washed with deionized water and dried.
3. The method for preparing the core-shell hierarchical nanoarray coating membrane according to claim 1, characterized in that: The volume ratio of the emulsion A: the solution B: the solution C is 9:10:
1.
4. The method for preparing the core-shell hierarchical nanoarray coating membrane according to claim 1, characterized in that: The core-shell hierarchical nanoarray inorganic ceramic material, binder, salt, deionized water and solvent are weighed in proportion, mixed and dispersed evenly to obtain a coating liquid, which specifically includes the following steps: Weigh inorganic ceramic material: binder: salt: deionized water in a weight ratio of 8:1:1:1 for use; Dissolving the binder in N,N-dimethylformamide, and sequentially stirring at high speed and continuously ultrasonicating to form a clear solution; The inorganic ceramic material, the salt and the deionized water are continuously ground, and then the clarified solution is added and continuously stirred to form the coating solution.
5. The method for preparing the core-shell hierarchical nanoarray coating membrane according to claim 1, characterized in that: The prepared core-shell graded nanoarray coating membrane comprises a base film (1), a core-shell graded nanoarray layer (2) and a binder (3); the core-shell graded nanoarray layer (2) is fixed to the upper end surface of the base film (1) by the binder (3); the core-shell graded nanoarray layer (2) is in the form of a core-shell graded nanoarray composed of inorganic ceramic particles as cores and boehmite nanoarrays as shells.
6. The method for preparing the core-shell hierarchical nanoarray coating membrane according to claim 5, characterized in that: The binder (3) is in a non-agglomerated state with high porosity.
7. The method for preparing the core-shell hierarchical nanoarray coating membrane according to claim 5, characterized in that: The inorganic ceramic particles are any one of Al2O3, ZrO2, SiO2, TiO2 and ZnO2.
8. The method for preparing the core-shell hierarchical nanoarray coating membrane according to claim 5 or 7, characterized in that: The particle size of the inorganic ceramic particles is 100-150 nm.
9. The method for preparing the core-shell hierarchical nanoarray coating membrane according to claim 5, characterized in that: The binder (3) is at least one of polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyperfluoropropylene and polychlorotrifluoroethylene.
Citation Information
Patent Citations
Lithium ion battery composite diaphragm, preparation method thereof and lithium ion battery
CN112151728A
Secondary battery separator and manufacturing method thereof
JP6550159B1